2013
DOI: 10.2147/nrr.s37548
|View full text |Cite
|
Sign up to set email alerts
|

Health numeracy and health literacy within the context of management of patients with human immunodeficiency virus

Abstract: Health literacy, although an important topic in human immunodeficiency virus (HIV), often eclipses health numeracy, which may be equally important for those living with this disease. Health numeracy is the knowledge and application of numerical concepts in health decisions. In our synthesis of the literature, the emerging concept of health numeracy in relation to HIV disease management is reviewed within the context of health literacy. Specifically, we examine health literacy and numeracy by gender, race, educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…This result may be explained by the fact that the interviewer asks the question to the elderly about what appears on the card, and this may help to improve their level of understanding. Still about these skills and control of diabetic disease, study with (n=383) diabetes (DM2) showed that a poorer blood glucose control was associated with low levels of mathematics or numeracy among participants (29) . But even so, it is visible by the results of this study that the reading comprehension was more committed to the applied test, suggesting that how the written information are delivered to users in the health service, can not be understood by them, or are written in a way that requires higher education, or may also contain words that hinder understanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result may be explained by the fact that the interviewer asks the question to the elderly about what appears on the card, and this may help to improve their level of understanding. Still about these skills and control of diabetic disease, study with (n=383) diabetes (DM2) showed that a poorer blood glucose control was associated with low levels of mathematics or numeracy among participants (29) . But even so, it is visible by the results of this study that the reading comprehension was more committed to the applied test, suggesting that how the written information are delivered to users in the health service, can not be understood by them, or are written in a way that requires higher education, or may also contain words that hinder understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the population that has higher chances of having low FHL, the highlights are the elderly, those who receive low wages, the unemployed, people with low education, cognitive, auditory and visual impairment, ethnic minorities groups and immigrants (29)(30) . In a Brazilian study (10,12) about the FHL, the researchers recommend its assessment of primary health care and the possibility of its inclusion in the agenda of public policies to strengthen health promotion actions, similarly to what happens in developed countries such as the US, Canada, UK, Australia, among others.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious limitation of self-reported health information is that these data are subject to recall bias, coupled with poor health literacy and numeracy (Gakumo, Vance, Moneyham, Deupree, & Estrada, 2013). In the larger parent study, electronic medical chart extraction will be performed to verify self-reports in the entire sample.…”
Section: Methodsmentioning
confidence: 99%
“…Variability in literacy, health numeracy, and health literacy of the study sample could have impacted the accuracy of self-reported data and may have impacted the study findings (Gakumo, Vance, Moneyham, Deupree, & Estrada, 2013). As the medical community strives to achieve improved patient-centered health outcomes, additional steps to explore aspects of symptom burden are warranted.…”
Section: Limitations and Future Researchmentioning
confidence: 99%